1993
DOI: 10.1111/j.1365-3016.1993.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

First report from the Plunket National Child Health Study: smoking during pregnancy in New Zealand

Abstract: The Plunket National Child Health Study is a 5-year longitudinal study of a birth cohort of 4285 children born in New Zealand during 1990-1991. This paper describes the major lines of epidemiological research, the methods and study design, and reports on the demographic data of New Zealand children. During this first report from the Plunket Child Health Study, we examine on the smoking rates of New Zealand mothers during pregnancy. Overall 33% of mothers smoked during pregnancy. Particularly high rates were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…Parental resistance was mainly apparent in disadvantaged populations [1,7,8,9,16]. Infants of socio-economically deprived families remained more highly exposed to sleeping prone and maternal smoking [2,3,12,16]. These ®ndings were consistent with the known association between impoverished social and economic situations and an excess in both infant mortality [2±4, 9±11, 13,15,16] and SIDS [11].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Parental resistance was mainly apparent in disadvantaged populations [1,7,8,9,16]. Infants of socio-economically deprived families remained more highly exposed to sleeping prone and maternal smoking [2,3,12,16]. These ®ndings were consistent with the known association between impoverished social and economic situations and an excess in both infant mortality [2±4, 9±11, 13,15,16] and SIDS [11].…”
Section: Introductionsupporting
confidence: 75%
“…When interpreting our data, several methodological caveats should be considered. First, the selection of risk factors was based on messages from the literature [2,6,9,13,15] and in the local risk-reducing campaigns. Other risk factors, such as bed sharing [5] or bottlefeeding [17] were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…11 Yet, in the early 1990s one-third of pregnant New Zealand women were still smoking. 12 The serious adverse effects associated with maternal smoking in pregnancy, coupled with its preventable nature and relatively high prevalence, impelled the now defunct New Zealand Public Health Commission (NZPHC) to specify a goal to reduce the prevalence of maternal smoking in pregnancy to 20% or less by 2000. 13 Since 1991, reducing maternal smoking has also been widely promoted in a national SIDS prevention program.…”
Section: Rpk Ford and Cj Fordmentioning
confidence: 99%
“…However, we found a high rate of maternal smoking during pregnancy, and Maori mothers were almost twice (52%) as likely to smoke during pregnancy. National figures in 1990–1991 showed that Maori mothers were three times more likely to smoke than NZE during pregnancy based upon post‐natal self‐report (68% vs. 23%, respectively) . The rate of maternal smoking at birth among mothers in Taranaki was reported to be 20% in 2013 (maternal post‐natal self‐report) .…”
Section: Discussionmentioning
confidence: 99%
“…National figures in 1990-1991 showed that Maori mothers were three times more likely to smoke than NZE during pregnancy based upon post-natal self-report (68% vs. 23%, respectively). 34 The rate of maternal smoking at birth among mothers in Taranaki was reported to be 20% in 2013 (maternal post-natal self-report). 35 The available NZ data, based on a cohort that was almost all of NZE ethnicity, has shown that in comparison with children whose mothers did not smoke during pregnancy, children of women who did smoke had an increased BMI at age 3 years.…”
Section: Discussionmentioning
confidence: 99%